Underground writing : the London tube from George Gissing to Virginia Woolf - Welsh, Dave, 1952- (Liverpool University Press, 2010)
The purpose of this book is to explore the ways in which the London Underground was 'mapped' by a number of writers from George Gissing to Virginia Woolf. From late Victorian London to the end of World War II, 'underground writing' created an imaginative world beneath the streets of London. The real subterranean railway was therefore re-enacted in number of ways in writing, including as Dantean Underworld or hell, as a gateway to a utopian future, as psychological looking-glass or as place of safety and security.